Characteristics of PM2.5 pollutionin winter and spring of Beijing during 20092010 - Gu, Fang-ting; Min Hu; Yu Wang; Li, Meng-ren; Guo, Qing-feng; Wu Zhi, jun (China Environmental Science, 2016)
A comprehensive measurement was conducted to investigate thecharacteristics of particulate matter (PM) pollution in winter and spring of Beijing. 24-hour particle samples were collected from December to May, 20092010, and the chemical compositions of PM2.5 were analyzed. The average PM2.5 massconcentrations were (84.97+or-68.98)mug/m3 and (65.25+or-45.76) mug/m3 in winter and spring, respectively. Secondary inorganic aerosols, i.e. sulfate, nitrate, andammonium (SNA), and secondary organic aerosols (SOA) were dominant theparticulate matter, with the total fraction (SNA+SOA) of 49% and 47% in winter and spring, respectively. Due to the largesource emissionand unfavorable meteorological conditions such as low temperature, low wind speed, and high relative humidity; the contributions of secondary inorganic aerosols (NH4+. NO3. SO42) were enhanced during thepolluted days, and the nitratewas more enhanced on polluted days. The SOA was always the most importantorganic aerosolcomponentcontributedto PM2.5 in winter and spring. The contribution ofprimary organicaerosolsalso increased due tothe stagnant meteorological condition on polluted days.
Keywords: A8670G Atmosphere (environmental science); A9260H Chemical composition and chemical interactions in the lower; A9260M Particles and aerosols in the lower atmosphere; A9330D Asia; AD 2009; air pollution; atmosphere; atmospheric composition/ Beijing; China; Energy & Fuels; Environmental Sciences & Ecology (provided by Clarivate Analytics); Experimental/ aerosols; Geography; meteorological conditions/ A9260T Air quality and air pollution; Meteorology & Atmospheric Sciences; particulate matter pollution; PM2.5 mass concentrations; PM2.5 pollution characteristics; secondary inorganic aerosols; secondary organic aerosols; spring season; to 2010; winter season